About Takhcheia in the letter of commendation to Yakov and Grigory Stroganov dated may 30, 1574. - Korchagin P.A.; Samigulov G.Kh (Золотоордынское обозрение)
References to the Takhcheya region can be found in numerous sources dated the late 16th – early 17th centuries. This toponym aroused great interest among historians, but all attempts to localize this land had a very relative success until recently. Sometimes, even within the framework of one publication, two opposing opinions were expressed about which territories this notation was used at the end of the 16th century. In a recent article, one of the authors of this investigation made an attempt to analyze the information contained in the main source – a charter on lands given by Ivan IV to Yakov and Grigory Stroganov in 1574. This publication provides a more extensive historiographical review of the topic and analyzes the toponymy of the regions, adjoining from the south to the Chusovaya possessions of salt producers. As a result, the authors came to the conclusion that the name Takhcheya meant an ancient transport corridor connecting the Cis-Urals and Trans-Urals, in a broader sense, the European and Asian parts of the mainland, which went to the Southern Trans-Urals along the Chusovaya, Sylva and Ufa rivers in its upper reaches and went to north of the modern Chelyabinsk region. This is the most convenient place for crossing the Ural Range, in its lowest part, where the routes of historical roads passed, which in the Russian tradition were called the Kazan road. Several hydronyms and toponyms with the same root “takht/takhch” as in the name of Takhcheya, meaning “stop, parking place” have been identified here: the preserved names of places of traditional parking on trade routes. Thus, the assumption about the formation of the name in connection with the nature of the area, as a communication corridor and about the spread of the Takhcheya region in the South Trans-Urals, is confirmed. The Stroganovs were interested in joining the Takhcheya region to their possessions, since trade routes, that passed here, connected the Urals with Central Asia, in particular, Bukhara and Samarkand. It was quite tempting to take control of these roads, but to implement the letter of commendation granted in 1574 seemed not possible.